The Misallocation of Pay and Productivity in the Public Sector : Evidence from the Labor Market for Teachers - Bau, Natalie; Das, Jishnu (World Bank, Washington, DC, 2017)
This paper uses a unique dataset of both public and private sector primary school teachers and their students to present among the first estimates in a low-income country of (a) teacher effectiveness; (b) teacher value added (TVA) and its correlates; and (c) the link between TVA and teacher wages. Teachers are highly effective in our setting: Moving a student from the 5th to the 95th percentile in the public school TVA distribution would increase mean student test scores by 0.54 standard deviations. Although the first two years of experience, as well as content knowledge, are associated with TVA, all observed teacher characteristics explain no more than 5 percent of the variation in TVA. Finally, there is no correlation between TVA and wages in the public sector (although there is in the private sector), and a policy change that shifted public hiring from permanent to temporary contracts, reducing wages by 35 percent, had no adverse impact on TVA, either immediately or after 4 years. The study confirms the importance of teachers in low income countries, extends previous experimental results on teacher contracts to a large-scale policy change, and provides striking evidence of significant misallocation between pay and productivity in the public sector.